The optimal sequencing of postoperative chemotherapy and radiation therapy in patients with locally advanced or incompletely resected non-small cell lung cancer - Weyant, Michael J. (Journal of Thoracic Disease, 2018)
The National Comprehensive Cancer Network (NCCN) provide specific, evidence based guidelines for the treatment of non-small cell lung cancer (NSCLC) of any stage at presentation (1).